2012
DOI: 10.1590/s1414-98932012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Riscos psicossociais e incapacidade do servidor público: um estudo de caso

Abstract: Os fatores de risco psicossociais do trabalho (FRPT), como o estresse, as pressões patogênicas da carga de trabalho, as dificuldades nas relações socioprofissionais e as condições e a organização inadequadas do trabalho podem ser consideradas variáveis que interferem na saúde mental e física do trabalhador. A prevenção desses aspectos deve ocorrer por meio da sensibilização, conscientização, motivação e ação organizada dos atores sociais da empresa ou do órgão. Os servidores públicos estaduais de Santa Catarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
18

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
0
5
0
18
Order By: Relevance
“…Em estudo sobre fatores de risco psicossociais, Serafim et al (2012) ao citar Guimarães et al (2012) menciona que os riscos estressores ou demandas de trabalho, estão relacionados aos custos psicológicos e fisiológicos inerente à atividade laboral, como a sobrecarga quantitativa ou o conflito de papéis. Nesse sentido, a disposição e combinação entre estes fatores incidirão consideravelmente na a saúde dos trabalhadores.…”
Section: Resultsunclassified
“…Em estudo sobre fatores de risco psicossociais, Serafim et al (2012) ao citar Guimarães et al (2012) menciona que os riscos estressores ou demandas de trabalho, estão relacionados aos custos psicológicos e fisiológicos inerente à atividade laboral, como a sobrecarga quantitativa ou o conflito de papéis. Nesse sentido, a disposição e combinação entre estes fatores incidirão consideravelmente na a saúde dos trabalhadores.…”
Section: Resultsunclassified
“…It was possible to verify that professionals inserted in organizations presenting hierarchical strictness and power centralization, poor communication, difficulties in interpersonal relationships, lack of social support, insufficient recognition and rewards, and devaluation of subjectivities may experience more suffering, lack of motivation, dissatisfaction, and discontentment at work, thus representing psychosocial risks of work-related illness (5,18) .…”
Section: Values/practices Mean Standard Deviation Min -Max Valuementioning
confidence: 99%
“…Furthermore, organizations that present cultures characterized by constant pressure, increased productivity requirements, high workloads, inappropriate interpersonal relationships, lack of social support, inflexible schedules, and long working hours are associated with higher incidence of occupational accidents and adverse events related to patient care (18) . Within these organizations, workers may experience insecurity, career uncertainty, fear of unemployment, and conflicts related to work requirements, possibly associated with high levels of professional stress and occurrence of burnout syndrome (5) .…”
Section: Values/practices Mean Standard Deviation Min -Max Valuementioning
confidence: 99%
“…The worker often needs a psychic readaptation to deal with such an emotional load, which exceeds his/her real capacity, triggering mental disorders. 1 Millions of people suffer from any form of mental illness in the world, and its incidence is increasing progressively each year. 2 In Brazil, authors have revealed a high prevalence of these mental disorders in different studied populations.…”
Section: Introductionmentioning
confidence: 99%